2011
DOI: 10.1007/s10554-011-9996-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of bifurcation optimal viewing angles and bifurcation angles by three-dimensional (3D) quantitative coronary angiography

Abstract: Evaluation and stenting of coronary bifurcation lesions may benefit from optimal angiographic views. The anatomy-defined bifurcation optimal viewing angle (ABOVA) is characterized by having an orthogonal view of the bifurcation, such that overlap and foreshortening at the ostium are minimized. However, due to the mechanical constraints of the X-ray systems, certain deep angles cannot be reached by the C-arm. Therefore, second best or, so-called obtainable bifurcation optimal viewing angle (OBOVA) has to be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…However, a head‐to‐head study comparing 2D with 3D bifurcation software in this phantom model is lacking. The potential benefits of 3D over 2D bifurcation software is difficult to demonstrate in this model for the following reasons: (1) in the phantom model, stenoses are shaped concentric, while advantage of 3D are expected to be more pronounced when stenoses are elliptically shaped; (2) the phantom model is constructed in a horizontal plane, while in‐vivo the coronary arteries are curved around the heart, which would result in an expected benefit of 3D QCA over 2D QCA in terms of less foreshortening of the curved arteries; (3) in the bifurcation model the most optimal view, perpendicular to the bifurcation, is easily to obtain, while it has been shown in‐vivo that the optimal viewing angle for bifurcation lesions cannot be obtained in almost half of the cases, hampering accurate 2D bifurcation QCA assessment while this optimal view can be reconstructed with 3D bifurcation QCA software .…”
Section: Discussionmentioning
confidence: 99%
“…However, a head‐to‐head study comparing 2D with 3D bifurcation software in this phantom model is lacking. The potential benefits of 3D over 2D bifurcation software is difficult to demonstrate in this model for the following reasons: (1) in the phantom model, stenoses are shaped concentric, while advantage of 3D are expected to be more pronounced when stenoses are elliptically shaped; (2) the phantom model is constructed in a horizontal plane, while in‐vivo the coronary arteries are curved around the heart, which would result in an expected benefit of 3D QCA over 2D QCA in terms of less foreshortening of the curved arteries; (3) in the bifurcation model the most optimal view, perpendicular to the bifurcation, is easily to obtain, while it has been shown in‐vivo that the optimal viewing angle for bifurcation lesions cannot be obtained in almost half of the cases, hampering accurate 2D bifurcation QCA assessment while this optimal view can be reconstructed with 3D bifurcation QCA software .…”
Section: Discussionmentioning
confidence: 99%
“…Their findings were again confirmed by Bourantas et al [19], who showed stronger correlation between 3D-QCA and intravascular ultrasound (IVUS) in lumen dimensions (r = 0.8) than 2D assessed %DS (r = 0.34). Ultimately, the greatest advantage of 3D-QCA may be that it offers improved assessment of the absolute lumen dimensions including length, diameter, tortuosity, and optimal views [20,21] and not just %DS.…”
Section: Quantitative Coronary Angiographymentioning
confidence: 99%
“…With an accurate reconstruction of the geometry of the coronary artery and appropriate boundary conditions, CFD can compute the entire flow field (e.g., 13 ). But while software packages can obtain the 3D geometry of the coronary arteries directly, 6,26 CFD remains time consuming with conventional technology. To use WSS for decision support during an intervention, CFD must be performed within a limited time frame.…”
Section: Introductionmentioning
confidence: 99%